Study of Salinity Tolerance in Several Mutant Rice Lines Using Morphophysiological and Biochemical Approaches - Nur Hidayah; Didy Sopandie; Azri Kusuma Dewi (Department of Agronomy and Horticulture, IPB University, 2026)
Salinity is a major limitation to rice production. ‘Atomita 2’, a mutation-derived rice variety released in 1983, was originally reported to be salinity-tolerant, but detailed evidence of its tolerance remains limited. This study aimed to identify salinity-tolerant mutant lines of ‘Atomita 2’ and to characterize their morphological, physiological, and biochemical responses in the M4 generation under salt stress. The experiment was conducted in a greenhouse through two stages: initial screening of mutant lines under 60 mM NaCl and subsequent evaluation of selected genotypes for morphophysiological and biochemical traits. Screening identified 38 surviving genotypes. Salinity stress reduced plant height, tiller number, 100-grain weight, and grain yield, and decreased photosynthetic rate, stomatal conductance, transpiration rate, and SPAD value. In contrast, APX and CAT activities, proline, and MDA increased with NaCl concentration, indicating stress adaptation. ‘Atomita 90’ and ‘Atomita 146’ showed greater tolerance than ‘Atomita 2’ and ‘Pokkali’, as indicated by stress tolerance index values and their physiological and biochemical responses.